Novel tubeless supraglottic ventilation in a difficult paediatric airway - Ng Ruth; Budiman Maryam; Azman Mawaddah; Goh Bee-See (Egyptian Journal of Anaesthesia, 2018)
Introduction: Discussion and careful planning are essential between surgeon and anaesthesiologist before upper airway surgery, especially in paediatric patients with upper airway obstruction. Tubeless supraglottic ventilation is an accepted technique worldwide. Case: A 22-month old boy presented with upper gastrointestinal bleeding and right lung empyema with underlying pneumonia. He was treated for Haemolytic Uremic Syndrome secondary to pneumonia. The boy underwent upper gastroendoscopy under general anaesthesia for arrest of gastrointestinal bleeding and was kept intubated for 21 days. He was subsequently reintubated three days later for emergency video-assisted thoracoscopy, pleural stripping, and pus drainage under general anaesthesia. He was electively extubated on the third post-surgical day. Two weeks later, the patient developed stridor and suffered respiratory distress. A flexible fibreoptic scope revealed left vocal cord palsy. He was subject to emergency direct laryngoscopy and examination under general anaesthesia due to clinical suspicion of airway stenosis. Tubeless supraglottic ventilation was used and balloon dilatation with microlaryngeal surgery was successful. Conclusion: Tubeless supraglottic ventilation is a novel and useful method in short upper airway surgery.